The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1177/082585970802400404
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Patients in the Emergency Department

Abstract: Although end-of-life care is not a primary function of the emergency department (ED), in reality, many access this department in the later stages of illness. In this study, ED use by patients registered with the Capital Health Integrated Palliative Care Service (CHIPCS) is examined and CHIPCS patient characteristics associated with ED use identified. Overall, 27% of patients made at least one ED visit while registered with CHIPCS; 54% of these resulted in a hospital admission. ED visiting was not associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 18 publications
3
57
1
2
Order By: Relevance
“…Therefore without the physicians’ confirmation clients might otherwise wait. A previous study reported a similar finding [11]. In addition, clients with at least one ERVH had a longer survival time compared to clients without any ERVH.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Therefore without the physicians’ confirmation clients might otherwise wait. A previous study reported a similar finding [11]. In addition, clients with at least one ERVH had a longer survival time compared to clients without any ERVH.…”
Section: Discussionsupporting
confidence: 76%
“…Over half of these visits resulted in hospital admissions. The primary reasons for emergency room visits included pain and shortness of breath [11]. Similar reasons for emergency room visits have been documented in other countries [12-14].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…1 Many patients seeking ED care have advanced chronic illness that requires immediate aid for symptom distress, are experiencing acute change in their health status, or are brought to the emergency department by their caregivers who can no longer physically care for or psychologically cope with these sick family members. 4 As in many other critical care areas of the hospitals, heroic measures often are expected in the emergency department. Patient care plans that include only comfort measures or withholding and even withdrawing medical treatments are viewed as traumatic decisions for most ED clinicians and require an enormous amount of effort to implement.…”
Section: Introductionmentioning
confidence: 99%
“…This resonates with the UK government End of Life Care Strategy emphasis on improved recognition of an approaching death and advance care planning, with a view to increasing choice, particularly around the place of death 9. Palliative care assessment and interventions targeting ED users may facilitate achievement of this goal, as the ED will rarely be a preferred place of death 10 11. One palliative care service in Nova Scotia, Canada, which implemented an integrated ‘shared care’ model of palliative care, crossing all places of care (ie, hospital, community and hospice) reported a 7% reduction in the number of patients with cancer presenting to EDs in the year after the service started 12.…”
Section: Introductionmentioning
confidence: 99%